14. OUTCOMES OF LABOR INDUCTION AMONG PREMATURE OF RUPTURE OF MEMBRANE AT THE NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY (Vietnam Journal of Community Medicine, 2023)
Objective: To evaluate the effectiveness of induction of labor with oxytocin on pregnant womenwith premature rupture of membranes at the National Hospital of Obstetrics and Gynecology.Subjects and methodology: This is a descriptive study on 150 pregnant women with pretermrupture of membranes during the period from August 2021 to August 2022 at the National Hospitalof Obstetrics and Gynecology. Results: Gestational age from 37-41 weeks accounted for 83.3%, andfrom 28-31 weeks accounted for 1.3%. Cervical length at admission over 25mm accounted for 64%after labor induction was 18.7%. After induction of labor with oxytocin, the average vaginal deliveryrate was 69.3%, and cesarean section was 30.7%. Level 3 success rate is 69.3%, and the failure rateis 14%. The rate of amniotic infection was 3.3%, and neonatal infection was 2.7%. Conclusion:Induction of labor with oxytocin was very effective in the subjects studied at the National Hospital ofObstetrics and Gynecology, with meager rates of amniotic infection and neonatal infection. However,monitoring for signs of bacteremia and neonatal sepsis needs to be more concerned with reducingmorbidity and mortality after birth.
Keywords: Premature rupture of membranes, labor induction, National Hospital of Obstetrics and Gynecology.